Iklim Organisasi: Lingkungan Kerja Manusiawi - André Hardjana (Jurnal ILMU KOMUNIKASI, 2006)
Abstract: Organizational climate is a major concept of human relations for understanding human behavior under different environmental influences. The climate affects employees’ productivity as well as job satisfaction. The right climate serves as one of the most effective tools of the leader for motivating his subordinates. This article is a critical review of the concept of organizational climate and its theoretical models which were developed by major scholars. More importantly, it shows the way organizational climate leads to the emergence of organizational communication climate, which in turn leads to the concept of organizational culture.